2015
DOI: 10.1186/s12890-015-0146-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Idiopathic pulmonary fibrosis acute exacerbations: the non-steroid approach

Abstract: BackgroundIdiopathic pulmonary fibrosis acute exacerbation (IPF-AE) constitutes IPF’s most devastating event, representing the unexpected superimposition of diffuse alveolar damage of unknown etiology. Guidelines recommend high-dose steroids treatment despite unproven benefit. We hypothesized that previous immunosuppression and the administration of high-dose steroids adversely affect IPF-AE outcome.MethodsWe studied all consecutive patients hospitalized in our department for IPF deterioration from 2007 to Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 30 publications
(42 reference statements)
4
56
1
3
Order By: Relevance
“…DONAHOE et al [101] performed a pilot study to evaluate the efficacy of plasma exchange, rituximab and intravenous immunoglobulin for AE-IPF, and showed better one-year survival than historical controls without serious adverse events. On the other hand, based on the results of the PANTHER trial, which demonstrated that the combination of prednisone, azathioprine and N-acetyl cysteine was harmful for IPF [102], PAPIRIS et al [103] hypothesised that previous immunosuppression and the administration of high-dose steroids adversely affect outcome of AE-IPF, and studied a protocol of immediate cessation of immunosuppression (if any), best supportive care and broad-spectrum antimicrobials. Their uncontrolled results revealed that the steroid avoidance strategy might be of benefit.…”
Section: Therapeutic Measuresmentioning
confidence: 99%
“…DONAHOE et al [101] performed a pilot study to evaluate the efficacy of plasma exchange, rituximab and intravenous immunoglobulin for AE-IPF, and showed better one-year survival than historical controls without serious adverse events. On the other hand, based on the results of the PANTHER trial, which demonstrated that the combination of prednisone, azathioprine and N-acetyl cysteine was harmful for IPF [102], PAPIRIS et al [103] hypothesised that previous immunosuppression and the administration of high-dose steroids adversely affect outcome of AE-IPF, and studied a protocol of immediate cessation of immunosuppression (if any), best supportive care and broad-spectrum antimicrobials. Their uncontrolled results revealed that the steroid avoidance strategy might be of benefit.…”
Section: Therapeutic Measuresmentioning
confidence: 99%
“…4 In keeping with this, a recent observational study of AE-IPF reported that patients never treated with immunosuppressants and steroids before and after an AE-IPF present a higher survival rate than those treated with steroids. 5 Contrary to this, in their study, Arai et al…”
mentioning
confidence: 68%
“…5 However, in their study, three patients with AE-IPF and multiple events were included as 10 separate patients of AE-IPF. Furthermore, there was no significant difference in survival from the onset of the first event of AE between AE-IPF patients who had not (n = 6) and had (n = 11) been treated with corticosteroids (P = 0.640).…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing how powerful properly conducted studies financed by scientific sources such as the National Heart, Lung and Blood Institute are to provide medical knowledge and to reduce bias, we strongly believe that in IPF, a study similar to the CORTICUS and PANTHER studies, comparing the two arms of the steroid and nonsteroid approach in the therapeutic management of 'acute exacerbation' of IPF is greatly awaited by scientists and owed to the patients. Uncontrolled preliminary clinical data appear to shed doubts upon the steroids approach on IPF acute exacerbations [24] In conclusion, the scientific community needs evidence whether IPF 'acute exacerbations' represent an intrinsic process of the disease or not because this will have enormous diagnostic and most importantly therapeutic implications. Certainly, by changing approach, we are not going to save IPF patients but according to Hippocrates 'do not harm' them.…”
mentioning
confidence: 99%